A New Horizon for the Management of the Tourism Sector and Spa Towns in the Reflection of International and Domestic Research - Fejes, Judit Katalin; Katits, Etelka; Szabó, Zoltán (Acta Carolus Robertus, 2025)
In recent decades, tourism sector and spa towns have faced numerous new challenges that necessitate the integration of traditional and AI-driven preventive and proactive management tools. This study examines the effectiveness of management in spa towns, with particular emphasis on the differences and similarities between international contexts and Hungary, as well as the specific challenges posed by regional characteristics and tourism. Based on the primary and secundery research findings, recommendations are made for the integration of AI technologies and the further development of traditional methods to enhance the sustainability and competitiveness of spa towns. The study also highlights the role of regional differences in the success of management strategies and provides a detailed analysis of the social and ethical impacts of AI-driven tools. The research concludes that the synergy between traditional and modern management tools is crucial for ensuring the long-term sustainability of spa towns.
Keywords: spa towns; traditional and AI-driven management; preventive and proactive management